An energy, water and disease disaster management module: a technoeconomic feasibility analysis - Nicholson, Thomas J (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Intermittent energy and water supply are current challenges faced by many residents in South Africa. South Africa is one of the more water scarce countries in the world; this coupled with the lack of infrastructure makes it challenging to provide every citizen with their right to basic water and sanitation. With millennium development goal 7C not being addressed in many areas, residents experience sub-standard living conditions, which drastically increases the vulnerability of marginalised groups to epidemics. In the sustainable development goals improving sanitation and drinking water has been identified as one of the most effective and least expensive means of reducing fatalities and increasing public health. There is a need for a mobile laboratory that demonstrates power and water self-sufficiency, which is capable of on-site diagnosis and water treatment. The unit will have the ability to perform independent compliance monitoring of municipal water supply, treat inadequate water and provide surplus electricity to surrounding areas. A literature-based study was performed utilizing several scientific databases to identify current methods of power and water production in previous disaster management and humanitarian relief situations. Based on findings three example laboratories were theoretically designed; structural modelling, systems simulation and optimization and sensitivity analyses were performed with HOMER Pro, PackVol and SketchUp. A cost benefit analysis was performed with the social return on investment methodology. Novel human waste processing was performed with fly ash and simulated faeces. Bacterial species identification in ice samples was performed with the API 20E protocol and limited equipment as a proof of concept for field deployment. A hybrid system consisting of PV panels, a wind turbine and biomass generator showed promise for displaced humanitarian relief camps; with every 1 ZAR capital invested resulting in 3.13 ZAR social benefit. A system consisting of PV panels and a battery bank proved to have the least environmental impact and the grid supply laboratory showed a cheaper cost of energy alternative for needs provision. Fly ash showed potential as in nutrient recovery and as a fertility aid to soil. The units developed function as a means to increase disaster preparedness and humanitarian relief as well a means to improve quality of life for rural marginalize populations.
Keywords: Uncatalogued